Enabling membrane reactor technology using polymeric membranes for efficient energy and chemical production - Li, Yixiao (Kansas State University, 2018)
Membrane reactor is a device that simultaneously carrying out reaction and membrane-based separation. The advantageous transport properties of the membranes can be employed to selectively remove undesired products or by-products from the reaction mixture, to break the thermodynamic barrier, and to selectively supply the reactant. In this work, membrane reactor technology has been exploited with robust H₂ selective polymeric membranes in the process of hydrogenation and dehydrogenation. A state-of-the-art 3-phase catalytic membrane contactor is utilized in the processes of soybean hydrogenation and bio-oil hydro-deoxygenation, where the membrane functions as phase contactor, H₂supplier, and catalytic support. Intrinsically skinned asymmetric Polyetherimide (PEI) membranes demonstrated predominant H₂permeance and selectivity. By using the PEI membrane in the membrane contactor, soybean oil is partially hydrogenated efficiently at relatively mild reaction conditions compared with a conventional slurry reactor. In the hydroprocessing of bio-oil using the same system, the membrane successfully removed water, an undesired component from bio-oil by pervaporation. The more industrially feasible membrane-assisted reactor is studied in the alkane dehydrogenation process. Viable polymeric materials and their stability in elevated temperatures and organic environment are examined. The blend polymeric material of Matrimid® 5218 and Polybenzimidazole (PBI) remained H₂permeable and stable with the presence of hydrocarbons, and displayed consistent selectivity of H2/hydrocarbon, which indicated the feasibility of using the material to fabricate thermally stable membrane for separation. The impact of membrane-assisted reactor is evaluated using finite parameter process simulation in the model reaction of the dehydrogenation of methylcyclohexane (MCH). By combining tested catalyst performance, measured transport properties of the material and hypothetical membrane configuration, by using a membrane assisted packed-bed reactor, the thermodynamic barrier of the reaction is predicted to be broken by the removal of H₂. The overall dehydrogenation conversion can be increased by up to 20% beyond equilibrium. The predicted results are justified by preliminary experimental validation using intrinsically skinned asymmetric Matrimid/PBI blend membrane. The conversions at varied temperatures partially exceeded equilibrium, indicating successful removal of H₂by the blend membrane as well as decent thermal stability of the membrane at elevated temperatures with the presence of hydrocarbons. The successful outcome of membrane contactor and membrane-assisted reactor using robust polymeric membranes shows the effectiveness and efficiency of membrane reactors in varied application. The future work should be focusing on two direction, to further develop durable and efficient membranes with desired properties; and to improve the reactor system with better catalytic performance, more precise control in order to harvest preferable product and greater yield.
Keywords: Catalytic dehydrogenation; Three-phase hydrogenation; Gas separation membrane; Polymeric membrane; Membrane reactor; Thermally stable polymeric material